Increasing of Skin pH level in Childhood Atopic Dermatitis - Pedia Primadiarti; Rahmadewi Rahmadewi; Iskandar Zulkarnain (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2014)
Background: Atopic dermatitis (AD) has multifactorial etiologies such as genetic, environment, and imbalance of immunology basis.  AD is marked with skin barrier dysfunction, whichcharacterized by fillagrin mutation. Fillagrin itself has an important role in skin hydration and pH adjustment, so that its functional nor amount defect will lead to hydration and pH adjustment impair, as well as shown in AD phenotype. Purpose: To evaluatethe difference of skin pH in AD (lesional and non lesional area) and normal children. Methods:  Phase 1 study was descriptive observational study, to determinenormal skin pH in 98 children. The following phase 2 was observational analitic study in 38 AD patients todeterminepH level of atopic group (lesional and non lesional skin).Results: pH level of normal children skin was 4.86±0.461, lesional skin in AD was 5.86±0.564, and in nonlesional skin was 5.20±0.460. One way ANOVA test revealed value p=0.000, post hoc analysis value was p=0.000. Conclusions: Higher pH level was observed on AD patients. Skin pH is an important factor in the pathogenesis of AD, main concern in the treatment of AD is maintaining skin pH, which is important to reduce AD exacerbation.Key words: fillagrin, pH of atopic dermatitis,pH of normal children.